Combined Effects of Nitrogen and Plant Spacing on Tomato Yield - Himatkhwah, Rahimullah; Tanai, Zmarialay Tan; Salihi, Mohammad Seddiq; Ehsan, Qudratullah (Journal of Natural Sciences – Kabul University, 2025)
Nitrogen level and plant spacing are essential factors for tomato growth, yield, and fruit quality. Under the agro-climatic conditions of Kandahar, limited studies have been conducted on the interaction of these variables; therefore, an experiment was carried out using RCBD design with 12 treatments and three replications to determine the effects of different nitrogen levels and plant spacings on tomato yield. The results showed that the highest fruit length, diameter, and weight were obtained with a 50 cm spacing and the application of 150 kg/ha nitrogen. For achieving a higher tomato yield, the application of 150 kg/ha of nitrogen, combined with a 30 cm plant spacing, is recommended.